Pemanfaatan Ameliorasi dari Biochar Sekam Padi dalam Meningkatkan Kesuburan Tanah di Lahan Bekas Tambang Batubara - Septyani, Ika Ayu Putri; Hamdi, Fadil Hukama (UNIVERSITAS LABUHANBATU, 2022)
The utilization of ex-mining land for agricultural extensification is an opportunity to solve the problem of food and the environment. One way to improve the soil quality of ex-mining land is by providing organic matter from agriculture waste are biochar and cow manure formulation. The study aimed to determine the effect of the use of several organic matter formulations to improve the soil quality of Sawahlunto ex-mining coal land. This research was conducted at Agriculture Experiment Station, Andalas University, Padang. This research consisted of four formulations of organic matter (A = control, B = cow manure, C = Rice husk biochar, D = Rice husk biochar + Cow manure) with five replications. The treatment units were allocated based on Randomized Complete Design (RCD). The results showed that the application of rice husk biochar and cow manure can improve the soil quality of ex-mining coal land, especially pH value and CEC. Increasing of CEC and pH was support macronutrient availability such as, available P, N, K, Ca, Mg and Na. The addition of organic matter from cow manure plus rice husk biochar gave the best value to improving the chemical properties of ex-mining coal land. So, cow manure and biochar combination is the first recommendation to improve the chemical properties of ex-mining coal land to support sustainable agriculture.Keywords : biochar, cow manure, ex-mining coal, soil quality